Eye Problems Education In The First Level Health Facility (Fktp) In Order To Improve The Role Of Fktp In The Covid-19 Pandemic - Alfa Sylvestris; Aryani Vindhya Putri; Feny Tunjungsari; Patmawati (DokTIn MEDIKA Jurnal Pengabdian Masyarakat, 2025)
Background: FKTP as the first gateway for the community to obtain health services has a role in carrying out promotive and preventive functions as well as providing education to the community, especially to maintain health. Various problems in the community related to eye complaints in the era of the covid-19 pandemic are of special concern, such as complaints of red eyes. This complaint is often underestimated by the community so that it makes them go to the doctor in an already severe condition. FKTP as the frontline needs to understand and recognize various pink eye complaints as early as possible so that they can carry out appropriate and accurate therapy, and if necessary, make tiered referrals to ophthalmologists. Likewise with refractive errors which are often neglected, FKTP must strengthen its function in conducting initial refraction checks to avoid refractive errors in patients. Objective: This counseling is intended to help increase awareness of general practitioners who are at the forefront of FKTP on red eye disorders and refractive errors in patients in the era of the covid-19 pandemic. Methods: This activity consists of three stages, namely pre-test, counseling, and post-test, then data collection and evaluation. Results: The results of the evaluation of this activity were the increased knowledge of general practitioners regarding the problems encountered in FKTP, especially red eye and refractive errors. A total of 52 general practitioners (84.6%) had good knowledge after counseling about eye problems in FKTP, especially red eyes and refractive disorders.